1977
DOI: 10.1104/pp.59.6.1085
|View full text |Cite
|
Sign up to set email alerts
|

Zinc, Iron, and Chlorophyll Metabolism in Zinc-toxic Corn

Abstract: (9). Hydroponic studies using several species, including soybeans (1, 13) and navy beans (17), suggested that high nutrient Zn did interfere with Fe uptake and/ or translocation, resulting in manifestations of Fe deficiency. The addition of Fe to the growth medium of soybeans could overcome the effects of high nutrient Zn, suggesting a competition between Zn and Fe at some site (1).Examination of competition between Zn -and Fe necessitates separate analysis of the absorption of metals by the roots and transloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(15 citation statements)
references
References 14 publications
2
11
0
Order By: Relevance
“…The negative effects of the NPs on plants could be related to the release of ions from them and/ or their direct interactions with plants (Perreault et al, 2014;Rao and Shekhawat, 2014). However, the obtained results were in agreement with the fact that the excess Zn 2+ can cause delayed growth by the decrease or inhibition of photosynthesis and imperfections of many enzyme activities, leading to metabolic disorders (Rosen et al, 1977;Hossain et al, 2012).…”
Section: Effects On the Growth Of The Plantsupporting
confidence: 75%
“…The negative effects of the NPs on plants could be related to the release of ions from them and/ or their direct interactions with plants (Perreault et al, 2014;Rao and Shekhawat, 2014). However, the obtained results were in agreement with the fact that the excess Zn 2+ can cause delayed growth by the decrease or inhibition of photosynthesis and imperfections of many enzyme activities, leading to metabolic disorders (Rosen et al, 1977;Hossain et al, 2012).…”
Section: Effects On the Growth Of The Plantsupporting
confidence: 75%
“…It has been known for many years that excess Zn 2+ can lead to the retarding of growth (Rosen et al 1977). Heavy metals may induce the release of proteins, lipids, and element components of the thylakoid membranes, leading to malfunction of light-harvesting complexes and photosystem II.…”
Section: Discussionmentioning
confidence: 99%
“…Zn toxicity in Zea mays also causes chlorosis of the leaves which can be alleviated by increased supply of Fe; in this case, however, the Zn-induced chlorosis is not correlated with a decreased transport of Fe to the leaves (ROSEN et al 1977). It is suggested that in Zea mays the chlorosis may arise from FeJZn competition for an iron-requiring step in the biosynthesis of chlorophyll, as for example the enzymes t5-amino laevulinate synthetase and coproporphyrinogen reductase (Hsu and MILLER 1965;MACHOLD and STEPHAN 1969;DUGGAN and GASSMAN 1974).…”
Section: Zinc Toxicitymentioning
confidence: 91%